STRATEGI MENGATASI PEMBIAYAAN MURABAHAH BERMASALAH PADA PT.BPRS KABUPATEN NGAWI (PERSERODA) KANTOR KAS GENENG - Dwi Wahyuni, Melli (Commodity : Jurnal Perbankan dan Keuangan Islam, 2024)
Financing is funding provided by one party to another to protect a previously agreed investment. Providing clients with access to capital for investment purposes in accordance with Islamic sharia law is what Islamic financial institutions refer to as financing. In the Islamic financial system, a purchase and sale transaction known as murabahah is one way to finance a project. Although the profit-sharing system is the main selling point of Islamic banking, the term "Islamic bank with profit-sharing bank" is controversial because the majority of Islamic banking funding comes from murabahah and not mudharabah. One of the main instruments in Islamic banking, murabahah financing, poses serious risks to liquidity and credit. This study uses qualitative research methods, especially field research. Interviews and documentation methods are part of the data collection process. The results of this study indicate a number of problems with murabahah financing, such as lack of supervision, fluctuations in debtors' ability to pay, and other economic factors. A more proactive approach to economic monitoring, more effective internal and external supervision, and a program to restructure financing sustainably are components of this plan. By implementing this plan, PT. BPRS Ngawi Regency will be able to manage murabahah financing better and reduce the possibility of financing problems arising in the future.